Take your best shot Tim Grey tackles your digital darkroom questions - Grey, Tim (O'Reilly Media, 2008)
"For years, Tim Grey has been answering questions on digital photography topics in his popular "DDQ: Digital Darkroom Questions" daily email newsletter, at his various public speaking appearances, in hundreds of magazine articles, and in the Digital Darkroom Quarterly print newsletter." "Unlike most how-to guides, this book provides clear, informed answers to the questions serious photographers ask most often. It's in Q & A format, organized by subject, so you can look up any issue or, by browsing, find the answer to the very question you were hoping someone else might ask."--Jacket.